BS EN 60364-5-53 AMD2. Low-voltage electrical installations. Part 5-53. Selection and erection of electrical equipment. Devices for protection for safety, isolation, switching, control and monitoring. Clause 534 (3rd February 2022) - British Standards Institution
No abstract available